Methodological Prolegomena to Neoplatonic Proclus (412-485) II: Reference Text: About Plato’s Theology (Peri tês kata Platôna Theologias), H. D. Saffrey – L. G. Westerink, «Les Belles Lettres», Paris 1968, pp. 1,5.6-8,15 - Terezis, Christos (Études helléniques / Hellenic Studies, 2002)
This brief critical examination of a few key terms in Proclus’ Peri tês kata Platôna theologias is an addendum to a previously published brief article in the Études helléniques/Hellenic Studies (vol 9, no 1, pp. 169-178).